1997
DOI: 10.1128/aac.41.7.1521
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of cyanovirin-N, a novel human immunodeficiency virus-inactivating protein that binds viral surface envelope glycoprotein gp120: potential applications to microbicide development

Abstract: We have isolated and sequenced a novel 11-kDa virucidal protein, named cyanovirin-N (CV-N), from cultures of the cyanobacterium (blue-green alga) Nostoc ellipsosporum. We also have produced CV-N recombinantly by expression of a corresponding DNA sequence in Escherichia coli. Low nanomolar concentrations of either natural or recombinant CV-N irreversibly inactivate diverse laboratory strains and primary isolates of human immunodeficiency virus (HIV) type 1 as well as strains of HIV type 2 and simian immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
416
2
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 570 publications
(440 citation statements)
references
References 68 publications
13
416
2
6
Order By: Relevance
“…At low nanomolar concentrations cyanovirin-N irreversibly inactivates both laboratory strains and primary isolates of HIV-1 and HIV-2; in addition, cyanovirin-N aborts cell-to-cell fusion and transmission of HIV-1 infection. 2 The antiviral activity of cyanovirin-N has been attributed to a tight binding of the compound to the viral envelope glycoprotein gp120, which must result in a reduced infectivity of the virus as well as reduced capacity of virus-infected cells to fuse with uninfected cells. Cyanovirin-N should be further pursued as an anti-HIV microbicide, i.e., as a topical formulation in the prevention of genital HIV transmission.…”
Section: C Y a N O V I R I N -Nmentioning
confidence: 99%
“…At low nanomolar concentrations cyanovirin-N irreversibly inactivates both laboratory strains and primary isolates of HIV-1 and HIV-2; in addition, cyanovirin-N aborts cell-to-cell fusion and transmission of HIV-1 infection. 2 The antiviral activity of cyanovirin-N has been attributed to a tight binding of the compound to the viral envelope glycoprotein gp120, which must result in a reduced infectivity of the virus as well as reduced capacity of virus-infected cells to fuse with uninfected cells. Cyanovirin-N should be further pursued as an anti-HIV microbicide, i.e., as a topical formulation in the prevention of genital HIV transmission.…”
Section: C Y a N O V I R I N -Nmentioning
confidence: 99%
“…Perhaps the most significant reason that proteins from natural product extracts have not been studied more fully is the widely held belief that these bioactive molecules do not have the pharmacological characteristics necessary to become useful drugs [2]. Cyanovirin-N (CV-N) is a novel protein, originally isolated from cultures of the cyanobacterium (blue-green algae) Nostoc ellipsosporum [3], that has generated interest as a lead natural product for the chemotherapy of HIV infection [4]. CV-N is an 11-kDa protein with a primary amino acid structure that has no significant homology (less than 20 %) to any known protein.…”
Section: Introductionmentioning
confidence: 99%
“…CV-N shows a remarkable degree of stability and activity after several freeze-thaw cycles, as well as after treatment with organic solvents (CH 3 CN, CH 3 OH, DMSO), denaturants (8M GnHCl), detergents (0.5 % SDS), 0.5 % H 2 O 2 or even 15 * Corresponding author. min boiling [3]. In addition to being isolated from its natural source, CV-N was also expressed from recombinant DNA in Escherichia coli [5], and most of the experiments described below used the recombinant protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof-of-principle experiments have shown that it is possible to produce ribosomal metabolites in this way (Schmidt et al, 2005;Donia, Ravel, and Schmidt, 2008;Ziemert et al, 2010). Especially well studied is the heterologous expression of cyanovirin-N. Cyanovirin-N is a lectin comprising 101 amino acid residues, isolated from Nostoc ellipsosporum (Boyd et al, 1997). It has been found to be a fusion inhibitor, preventing infection with all HI virus types.…”
Section: Secondary Metabolitesmentioning
confidence: 99%